TECHNOLOGICAL QUALITY OF TWELVE MUSCLES FROM YOUNG LLAMAS (LAMA GLAMA) REARED UNDER AN EXTENSIVE PRODUCTION SYSTEM - Mamani Linares, Lindon W. (2013)
This study compared the technological quality of twelve muscles of llama that were raised in a grazing system. The llamas (n=10) were slaughtered using Bolivian standard procedures. Carcasses were stored for 24 h in a cold room (4 ºC). Muscles were removed from the left side of each carcass in the slaughter house. Five steaks (2.54 cm thick) were cut from each muscle. In each muscle was determined pH, holding capacity (WHC) and Warner-Bratzler shear-force (WBSF). No statistical difference was found in pH between muscles. Values of L* (lightness) and b* (tenor of yellow) in L. thoracis, L. lumborum and Semimembranosus were higher than those in Triceps brachii and Psoas major (p<0.05). The cooking loss percentage was lower in Infraspinatus and Longissimus thoracis (p<0.05). The WBSF value in the Semimembranosus, Semitendinosus, Quadriceps femoris and Biceps femoris muscles was higher (p<0.05) and in Infraspinatus was the lowest (p<0.05). Tenderness (WBSF), colour, and water holding capacity varied between muscles.colour (L*, a*, b*), water